ЗОГЕНДІ ФАКТОРЛАРДЫҢ ЖАНУАРЛАРДЫҢ ЭЛЕКТРОКАРДИОГРАММАСЫНА ƏСЕРІ (Experimental biology, 2015)
In the first by means of the spectral analysis in a winter season daily dynamics of an electrocardiogram of heart at rabbits in norm has been defined and at a hypoxemia, also were tap features chronostructure indicators of a teeth and is established that a teeth of an electrocardiogram within days subject fluctuations
Keywords: spectral analysis; electrocardiogram